Features of Catheter Treatment of Non-Isthmus-Dependent Atrial Flutter - Almiz, Pavlo O.; Kravchuk, Borys B.; Maliarchuk, Rostyslav H.; Perepeka, Eugene O.; Tymoshenko, Dmytro A.; Pokanevich, Alona V. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Atrial flutter (AF) is caused by the re-circulation of the wave of electrical excitation of the myocardium (reentry) around the anatomical substrate which circulates within the atrial tissues. This is always a macro re-entry. Such an anatomical barrier, around which circulation can occur, can be the superior or inferior vena cava, rings of the tricuspid or mitral valves, the mouth of the coronary sinus, pulmonary veins, postoperative scar. The aim. To determine the specifics of elimination, success rate, and long-term outcome with various preablation and postablation diagnostic techniques for non-isthmus-dependent atrial flutter (NIDAFL). Materials and methods. The study included 26 patients who underwent radiofrequency ablation of atypical NIDAFL. Results. As a result of radiofrequency ablation, a sinus rhythm was restored in 17 patients during the procedure. In 7 cases, when the typical, isthmus-dependent AF was removed, the tachycardia cycle and the morphology of the R wave changed. Mapping showed that in 7 cases the direction of the re-entry front changed, and instead of the circulation of excitation through the cavatricuspid isthmus, it then passed around the atriotomy scar. In 2 cases, a change in the cardiac cycle was observed after radiofrequency ablation, but the excitation circulation was the same around the atriotomy scar, only the tachycardia cycle increased. As a result of the use of our techniques, arrhythmia was eliminated in all 21 patients with an atriotomy AF during one procedure. Five patients with AF of a different localization of the re-entry circuit also had their arrhythmia eliminated, although 8 procedures (for five patients) were performed (on average 1.6). There were no complications. During the follow-up period of 1.8±0.7 years, 2 patients had a recurrence of arrhythmia, and they underwent a repeat procedure to eliminate the arrhythmia. One patient developed typical AF that had not been observed before, which was successfully eliminated. Conclusion. Catheter treatment of atypical NIDAFL is quite a non-trivial task, because, as our experience shows, several types of tachycardia occur in a significant number of patients. In cases of restoration of sinus rhythm as a result of the application, it is necessary to check the inducibility of another arrhythmia. But despite everything, catheter removal of NIDAFL is quite effective, especially for atriotomy AF, although it requires more X-ray exposure and a relatively large number of applications. The use of navigation systems has helped to improve the results of such interventions in more complex cases.